Pulsed radiofrequency in patients with chronic shoulder pain - Radiofrequenza pulsata in pazienti con dolore cronico della spalla - Antonino Genovese; Luigi Cardia; Epifanio Mondello; Antonino Fugazzotto; Salvatore Bartolone; Maria De Florio; Carmelo Costa (Publiediting, 2017)
The purpose of this study is to evaluate the efficacy and safety of suprascapular nerve pulsed radiofrequency, in patients affected by chronic shoulder pain. In the study were included sixteen (16) patients affected by chronic shoulder pain for a period of more than six months. Of which: 3 suffering from frozen shoulder, 5 for lesions (injury) of the rotator cuff, and 8 for osteoarthritis. After a favorable response to a diagnostic suprascapular nerve block (pain relief > 50% NRS), PRF neuromodulation was performed. Shoulder pain and quality of life were assessed using a Numeral Rating Scale (NRS), before the diagnostic block and every month after PRF neuromodulation for a 6-month period. The mean NRS score in all (16) patients before PRF was 6.75±1.05, and the scores at 6-month follow-up were 1.30±0.50. A significant pain reduction (p<0.001) was observed. Pulsed radiofrequency of the suprascapular nerve is an effective treatment in patients affected by chronic shoulder pain, providing a relatively long period of pain relief.